Espelhos de papel: arte, artes gráficas e impressões do Rio de Janeiro oitocentista - Varela, Eduardo Alberto de Souza (2011)
This work presents an overview of the graphic arts in Brazil, from the external influences which marked its origins throughout its development along the nineteenth century. General ideas about art and its manifestations, as well as the opinions of renowned scholars on the subject have been discussed, aiming at a better understanding of the theme. Early image reproduction and printing techniques then in current use, and the new image-capturing art of photography have been studied. Artists and printers have either passed by or established themselves in Rio de Janeiro, leaving a rich technical and artistic legate. City landscape and everyday life as seen by these visitors, their insertion in the artistic movements of the time and the political meaning of their achievements are also within the scope of the work. It has been sought, at last, to reevaluate certain longestablished ideas on the work of art and its reproduction